Digital Marketing Application Strategy for Textile MSMEs in Pasar Baru Bandung and Its Implication on Purchasing Decisions and Consumer Word of Mouth - Nadia Muldiani; Andre Suryaningprang; Deni Hamdani; Dadan Abdul Aziz Mubarok (International Journal of Marketing & Human Resource Research, 2026)
Textile MSMEs in the Pasar Baru area of Bandung are facing difficulties in maintaining their competitiveness as consumer behavior continues to shift toward relying on digital media as a key source of information and purchase consideration. The analysis focuses on how textile MSME owners apply digital marketing strategies and how these practices influence consumer purchasing decisions and the spread of word-of-mouth (WOM). A descriptive qualitative approach was applied, utilizing in-depth interviews, direct observation, and documentation analysis involving MSME owners and related consumers. The findings indicate that using social media, online marketplaces, and digital review platforms enhances business visibility, improves engagement with consumers, and builds favorable product perceptions. These factors collectively drive purchasing decisions and stimulate both traditional WOM and electronic WOM. Conversely, MSMEs that do not adopt digital strategies face limitations in market reach and dependency on traditional marketing methods. This study concludes that digital marketing is a strategic instrument that can increase the competitiveness of textile MSMEs in Pasar Baru Bandung, and the optimization of digital technology utilization becomes an important factor in strengthening marketing performance in the era of digital transformation.